Study on China Telecom Billing-Side Real-Time Information and Data Synchronization - Jia Liu; Lujing Xia (Dianxin kexue)
The two-tier operation mechanism, and local operation and maintenance convention of China Telecom made the headquarter lack of customer information, price plans, sales management, product data etc. The way was discussed that uploading the data scattered in each province to the headquarter IT center in real time and synchronously. Therefore a method was proposed which combined data files with message increment. Through the implementation of program design, key technology and performance optimization, the initial goal that“basic data can be changed simultaneously in the two-tier, management of the core meta data can be centralized”was achieved.